Pedagogical potentialities of podcasts in learning: reactions from K-12 to university students in Portugal. - Carvalho, Ana Amélia Amorim (2013)
This paper stresses the use of podcasts in learning, describing different types of podcasts in learning situations, namely knowledge content, instructions, and feedback to students’ assignments. Four studies are described involving students from 9th grade, 11th grade, undergraduates and graduates students. Each study deals with a different type of podcasts and we analysed learners’ acceptance or rejection. The students recognized the pedagogical value of podcasts in learning. The 9th grade students enjoyed the activity of creating their own podcasts and recognized its impact in their learning. The 11th grade students preferred to listen to podcasts than reading the content in a book. Most of the undergraduate students liked to listen to the instructions, but a few would prefer to get them in a written text, as they are used to read. The graduate students enjoyed listening to feedback to their assignments, mentioning that it was unusual, but it kept their interest and attention, and it gave a sensation of proximity to the teacher.